Obama, US Foreign Policy and the Dilemmas of Intervention - Fitzgerald, D. author. aut Link
VIII, 151 p.
Keywords: This timely study analyses the ways in which competing ideologies and cultural narratives have influenced the Obama administration's decision-making on Iraq, Afghanistan, Libya and Syria, situating these decisions within the broader history of American foreign policy.